Pelatihan Dan Pendampingan Digital Marketing Bagi UMKM Di Desa Ambulu Kecamatan Sumberasih Kabupaten Probolinggo - Amisha Novita Arif; Yuniningsih Yuniningsih (Universitas Muhammadiyah Manado, 2023)
Technological developments have created many opportunities for many sectors. One of them is the opportunity for SMEs. A business that utilizes technological media has a great opportunity to develop. The use of technology in a business can be done with digital-based marketing or what is commonly called digital marketing. Digital marketing or digital marketing is an online promotion and marketing activity by utilizing social media, e-commerce, and other digital platforms. This research focuses on digital marketing assistance and training for MSMEs in Ambulu Village, Sumberasih District, Probolinggo Regency. This study aims to identify and analyze the implementation of digital marketing in promotional and marketing activities carried out by MSME actors in Ambulu Village. The method used in this research is descriptive qualitative using observation and focused discussion techniques to collect the data. Based on the results of the research, the implementation of digital marketing in Ambulu Village has been going well, but there are still obstacles encountered, namely that there are still several MSME actors who lack understanding of technology.